Working for God (and Country): Religious Education and Economic Diversification in the United Arab Emirates - Sharif Ibrahim El Shishtawy Hassan (15445394) (2023)
While the role of state formation, British withdrawal, and the discovery of oil in transforming social life in the United Arab Emirates (UAE) has received considerable attention, scholars have focused less on the role the state has played in leading particular forms of social change. In this chapter, we explore how the Emirati state has attempted to cultivate certain values among its citizens to support its goal of economic diversification. We find that the state has reformed its national education curriculum in an effort to equip Emirati youth with both the requisite skillset for transitioning to a knowledge economy and the mindset necessary to accommodate such a transition. Analyzing 24 Islamic education textbooks, totaling nearly 5,400 pages, we find that the revised curriculum reflects a concerted effort on the part of the Emirati state to develop a Muslim work ethic by framing capitalist values such as productivity and hard work as divinely ordained. Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_23